Relationship between principals’ emotional competence and teachers’ job satisfaction in selected secondary schools in Bangladesh - Chowdhury, Mamataz Sharmin (2014)
The purpose of this quantitative descriptive study was to examine the relationship between principals‟ emotional competence and teachers‟ job satisfaction in the secondary schools in Bangladesh. Recent studies found that emotional competence is a necessary skills for leadership, which can be improved through training. Research on emotional competence specific to principals of high performing and low performing schools still evolving. At present theoretical linkage between emotional competence and job satisfaction at the school levels are not fully established by past researchers. This is a descriptive correlational study conducted using a survey method consisting of 367 randomly selected school teachers. This study utilized Daniel Goleman‟s emotional competency inventory -2 (ECI-2) as independent variable and Spector‟s (1997) job satisfaction survey instrument as dependent variable, which met the standard of validity and reliability. The result of descriptive statistics revealed that principals‟ emotional competence level was moderate as perceived by teachers. However, teachers reported moderate level of job satisfaction in high performing and low performing schools. The seven constructs of job satisfaction empowerment and professional development received the highest mean score and benefit the lowest. The independent t-test showed that principals‟ emotional competence and teachers‟ job satisfaction had significantly higher scores in high performing schools than in low performing schools. The results of this study revealed that teachers differ significantly in satisfaction in relation to age, and years of experience. However, the present study findings indicate that there are no significant differences in job satisfaction in relation to educational qualification, and gender. The Pearson correlational analysis of the study found a moderate positive correlation (r = .694, p> .05) of emotional competence and job satisfaction. The statistically positive correlation between principals‟ emotional competence and teachers‟ job satisfaction suggested that the principals who were emotionally competent tended to be associated with teachers who were satisfied with their job. The multiple regression analysis revealed that self-awareness, self-management, and relationship management are significant predictors of teachers‟ job satisfaction. However, social awareness was not included as a significant predictor of job satisfaction. The overall regression model was successful in explaining approximately 49.5% variance in teachers‟ job satisfaction. Based on the findings it is recommended that policy makers should utilize appropriate strategies to improve principals‟ knowledge and abilities and elevate the level of teachers‟ job satisfaction. This study found empirical proof that teachers are more likely to show higher levels of job satisfaction if they perceived their principals exhibit emotional competence. The findings of this study may assist administrators, and policy makers to identify factors that influence job satisfaction, and then steps can be implemented to provide teachers with what they need to achieve and maintain job satisfaction. In reviewing the overall results of the study it would appear to provide tentative evidence which suggests that the principals may achieve improved performance if the emotional competence domains of self-awareness, self-management and relationship management are included in their selection and professional training criteria. Policy makers should utilize appropriate strategies to improve administrator knowledge and ability and elevate teachers' job satisfaction.